The Routledge handbook to the history and society of the Americas - Kaltmeier, Olaf, 1970- (Routledge handbooks., 2019)
"This handbook explores the history and society of the Americas, placing particular emphasis on collective and intertwined experiences. Forty-four chapters cover a range of concepts and dynamics in the Americas from the colonial period until the present century."--Provided by publisher.